2018
DOI: 10.1002/acn3.668
|View full text |Cite
|
Sign up to set email alerts
|

CSF TACI and BAFF levels in patients with primary CNS lymphoma as novel diagnostic biomarkers

Abstract: We used an enzyme‐linked immunosorbent assay to measure pretreatment B cell‐activating factor belonging to the tumour necrosis factor family (BAFF) and transmembrane activator and CAML‐interactor (TACI) levels in CSF and serum collected from patients with primary central nervous system lymphoma (PCNSL) and control groups. The decision tree analysis of CSF TACI and BAFF levels for patients with a PCNSL diagnosis showed 100% sensitivity and 100% specificity when we attempted to differentiate PCNSL from glioblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Several other potential biomarkers for PCNSL have been identified in the past. The proteins neopterin [13], CXCL13 [11], IL-10 [912], IL-6 [9, 10, 12], β-microglobulin [10, 14], osteopontin [15], BAFF [30], sTACI and sBCMA [31], and sCD27 [16] have been analyzed for their potential as diagnostic biomarkers. Their reported sensitivities for the diagnosis of PCNSL ranged from 68% (ß2-microglobulin [14]) to 100% (sCD27 [16]) with specificities ranging from 63% (IL-6 [9]) to 100% (IL-10 [9]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other potential biomarkers for PCNSL have been identified in the past. The proteins neopterin [13], CXCL13 [11], IL-10 [912], IL-6 [9, 10, 12], β-microglobulin [10, 14], osteopontin [15], BAFF [30], sTACI and sBCMA [31], and sCD27 [16] have been analyzed for their potential as diagnostic biomarkers. Their reported sensitivities for the diagnosis of PCNSL ranged from 68% (ß2-microglobulin [14]) to 100% (sCD27 [16]) with specificities ranging from 63% (IL-6 [9]) to 100% (IL-10 [9]).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the study design, the composition of the control cohort (control patients with focal brain lesions of malignant, inflammatory, and infectious origin; control patients without focal lesions; healthy controls), the quantification method, the chosen cut-off level, and the number of patients included. For example, Mizutani et al recently present the value of BAFF and TACI as a biomarker for CNSL with a reported sensitivity and a specificity of 100% [30]. However, their retrospectively collected data included only nine PCNSL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small sample study of nine patients with PCNSL, the combination of elevated levels of CSF BAFF and its receptor TACI revealed 100% sensitivity and 100% specificity for the diagnosis of PCNSL. 45 …”
Section: Novel Diagnostic Markers For Pcnslmentioning
confidence: 99%
“…In line with these findings, our group has demonstrated a high expression of BAFF as well as its receptors in PCNSL specimens (22), indicating a potential role for autocrine BAFF/BAFF-R signaling in the pathophysiology of PCNSL. Patients with PCNSL showed significantly higher BAFF CSF levels when compared with other focal brain lesions (23,24). However, patients with PCNSL also exhibit higher CSF levels of soluble TACI and soluble BCMA (25), possibly limiting the local availability of BAFF (26).…”
Section: Introductionmentioning
confidence: 98%